IMPLEMENTASI PRINSIP PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS DALAM NOVEL AKU TERLAHIR 500 GRAM DAN BUTA KARYA MIYUKI INOUE - Oemiati, Sri (Proceeding SENDI_U, 2016)
Readiness of parenting and positive reception of a mother to a disable child will help the growth and progress ofchildren in terms of both academic and other developments. This paper focuses on the Implementation Principles ofLearning Disable Children in the novel Aku Terlahir 500 gram dan Buta by Miyuki Inoue. This paper aims todescribe the implementation of learning principle of the main character as a disable child in the novel. It is basedon the theory proposed by Bambang Putranto. The purpose of the study is to add insight on the principle of learningfor disable children as well as expanding knowledge on the analysis of literary studies. The data collection includesthe close reading, observations an written documents. The steps of the study consist of 1) planning 2) data collection3) data processing 4) conclusion, and 5) the writing of the report. According to analysis conducted by the writer, itis concluded that the principle of learning undertaken by Miyuki’s mother in educating her blind child is theprinciple of concreteness/sensory experience, the totality, and the principle of independent activity.Kata Kunci: ABK (anak berkebutuhan khusus), prinsip kekonkretan, totalitas, aktivitas mandiri